Time to Evaluate the Clinical Repercussions of Zika Virus Vertical Transmission? A Systematic Review - Amaral, Yasmin Notarbartolo di Villarosa do; Malacarne, Jocieli; Brandão, Paloma Glauca; Brasil, Patrícia; Nielsen-Saines, Karin; Moreira, Maria Elisabeth Lopes (Frontiers in Psychiatry, 2021)
Background: Vertical transmission of Zika Virus have been associated with several clinical features in newborn infants. The goal of the present review is to analyzes the current state of knowledge about the clinical repercussions of vertical exposure to ZIKV in children up to 3 years of age. Methods: A systematic review of studies was carried out, without the restriction of language or date of publication, identified in the databases PubMed, Virtual Health Library (BVS), Scopus, and Web of Science and the catalog for CAPES theses and dissertations. According to the proposed flowchart, the bibliographic search resulted in 1,563 papers. Of these, according to the eligibility criteria, 70 were selected for the systematic review; all were published from 2016 to 2021. Results: In regards to clinical findings, 19 papers evaluated clinical imaging alterations, 21 ophthalmic manifestations, and 39 evaluated the central nervous system; of these, 15 analyzed neuropsychomotor development. The remainder evaluated audiological (n=14), nutritional (n=14), orthopedic (n=7), cardiorespiratory (n=5), genitourinary (n=3) or endocrinological (n=1) manifestations. Conclusion: It is critical for studies to continue monitoring children with antenatal ZIKV exposure as they grow, given the unknown long term repercussions of ZIKV and the recognized complications of ZIKV infection during pregnancy. Broader descriptions of observed clinical findings are also important in order to characterize the entire spectrum of disease in children. PROSPERO REGISTER: CRD42020205947